DENGUE EPIDEMICS: KNOWLEDGE PERHAPS IS THE ONLY KEY TO SUCCESS - Ramzan, Musarat; Ansar, Ambreen; Nadeem, Sadia (Journal of Ayub Medical College Abbottabad, 2015)
Background: Dengue fever/dengue haemorrhagic fever is a re-emerging vector-borne viral illness that is endemic in Tropics and poses a major public health burden in many countries of South East Asia, The objectives of the study were to correlate the dengue fever knowledge and preventive practices with age, gender, education, occupation and marital status of people of Wah Cantt. and to determine the association between knowledge level and preventive practices. Methods: This cross-sectional Survey was done in Wah Cantt from July to Dec 2011. Three hundred and sixty-three participants were selected through Stratified Random Sampling. Data on the knowledge and practice of the participants was collected by using structured questionnaire by the researcher. Knowledge and preventive practices were given scores on each correct response and participants were categorized into different groups according to their scores, i.e., excellent, good, poor and negligible. Associations were computed using Chi-square and Bivariate Correlation. p-value<0.05 was taken significant. Results: Mean age was 35.7±12.1 years. More participants were male (64.5%). Male sex, old age, employment without specific qualification and being parents had significant associations with both levels of knowledge and preventive practices. Level of knowledge was highly associated with levels of practice X2=79.1, df=9, p=0.000 and r=0.464 and p=0.000. Conclusion: The knowledge and preventive practices of people are related to their gender, marital status, age and occupation. Unexpectedly education has no association with knowledge or better preventive behaviour. Preventive practices get better where knowledge levels are more, emphasizing the need of community education programmes. Keywords: Dengue, knowledge, preventive practices, demographic characteristics, gender, marital status, age, occupation, education, Wah Cantt